Family Motivation as a Determinant of Independence in Elderly Care for Non-Communicable Diseases in Gorontalo - Rona Febriona; Rosmin Ilham (Nutrition Science and Health Research, 2026)
Family motivation is an important factor influencing independence in elderly care, especially among those with non-communicable diseases (NCDs). This study aimed to analyze the relationship between family motivation and independence in caring for elderly NCD patients. A cross-sectional study was conducted in March 2025 at the Tolangohula Health Center, Gorontalo Regency, Indonesia. A total of 89 families caring for elderly NCD patients were recruited using total sampling. Data were collected through structured questionnaires covering demographics, family motivation, and family independence. Validity and reliability tests confirmed that all instruments demonstrated strong internal consistency and were suitable for use in the study. Data were analyzed using the Chi-Square test with a significance level of p < 0.05. The results showed that most families had strong motivation (60.7%) and high independence (Level IV, 60.7%). Families with strong motivation predominantly achieved Level IV independence (85.1%), while those with moderate motivation tended to fall within Levels III and II. The Chi-Square analysis revealed a significant relationship between family motivation and family independence (p < 0.001). These findings indicate that stronger family motivation is significantly associated with higher independence in elderly NCD care. Strengthening family education and empowerment programs within community nursing services is recommended to enhance caregiving capacity and improve health outcomes among elderly individuals with chronic diseases.